The role of nanotechnologies in diagnostics and treatment of female reproductive system cancer - Z. R. Faizullina; A. A. Zhilenko; A. Kh. Islamgulov; E. A. Chernaya; A. I. Tochieva; A. A. Sanova; D. A. Dryaeva; S. Sh. Khaknazarov; T. R. Gazizov; M. M. Otadzhonov; Kh. A. Merzhoeva; E. V. Malikova; et al. (Акушерство, гинекология и репродукция)
Introduction. By enhancing detection accuracy, therapeutic effectiveness and minimizing side effects, nanotechnology may contribute to improve diagnostics and treatment of patients with female reproductive system cancer.Aim: to summarize current literature data and assess а role of nanotechnology in treatment of cervical cancer (CC), ovarian cancer (OC), endometrial cancer (EC) and reveal gaps requiring further research.Materials and Methods. The search was carried out in the electronic databases PubMed/MEDLINE, Google Scholar and eLibrary using the following keywords: “gynecological cancer”, “targeted therapy”, “cervical cancer”, “ovarian cancer”, “endometrial cancer”, “nanotechnology”, “nanoparticles”. All works were published between 2011 and 2024.Results. Nanocarrier-based drug delivery systems represent a promising approach to the treatment of female reproductive system oncology, providing precise drug delivery directly to tumor cells. Such systems, including liposomes, nanoparticles, micelles, and dendrimers, are characterized by advanced efficiency, reduced toxicity, as well as the opportunity for controlled release of active components. Nanotechnologies increase the effectiveness of vaccines by prolonging their half-life, affect the СС microenvironment and potentiate the antitumor immune response with minimal toxicity. Nanovaccines are capable of delivering antigens and adjuvants directly to immune cells, enhancing immune response and improving ОС treatment results. Nanotechnologies show prominent potential in improving EC treatment despite that their role in this context remains understudied compared to other types of female reproductive system cancer.Conclusion. Nanoparticles can carry both conventional drugs as well as protein- and nucleic acid-based systems directly to cancer cells. However, only a few nanoparticle-based treatments for female reproductive system cancer have been approved for use. The field is making significant progress toward more effective and widely available treatments.